The Use of Learning Cell on Students' Reading Comprehension - Rukmiyati, Yurita (Journal of English Teaching and Linguistics Studies (JET Li), 2022)
Reading comprehension is a process of constructing meaning from the text during reading. Students not only can read the text but also comprehend the writers message in the text. However, the difficulty of comprehending text during reading is a problem for students. Learning Cell technique is the solution to solve the problem. The aim of this research is to investigate the use of Learning Cell technique on students reading comprehension. In conducting this research, the researcher applied pre-experimental method and one group pretest and posttest design. This research is conducted in the eleventh-grade students of SMA Yadika 7 Bogor. There were 29 students as the sample of this research by using random sampling. The result shows that based on t-table, the degree of freedom of 28 at significant level of 0.05 is 2.048. However, the value of t-test is 6.09. From the comparison between the value of t-test and the t-table, it can be concluded that the value of t-test is higher than t-table (6.092.048). Thus, the alternative hypotheses of this research (Ha) is accepted.  Therefore, Learning Cell technique affects students reading comprehension.